Antibodies to endothelial cells in Behçet's disease: cell-binding heterogeneity and association with clinical activity. Issue 4 (April 1994) - Cervera, R; Navarro, M; López-Soto, A; Cid, M C; Font, J; Esparza, J; Reverter, J C; Monteagudo, J; Ingelmo, M; Urbano-Márquez, A
Abstract : OBJECTIVES--To investigate the prevalence and characteristics of antibodies to endothelial cells (aEC) from large vessel and from microvasculature in a group of patients with Behçet's disease (BD) to determine the relationship of these antibodies with clinical and laboratory features of the disease. METHODS--Thirty patients with BD were prospectively and consecutively studied. The aEC were determined by enzyme-linked immunosorbent assay (ELISA) using endothelial cells derived from human umbilical vein (large vessel) as well as from retroperitoneal adipose tissue (microvasculature). RESULTS--Fifteen patients (50%) had aEC, either directed to large vessel [8(26%) patients] or microvascular [13(43%) patients] endothelial cells. The percentage of active patients was significantly higher in the aEC-positive group [12(80%) patients] compared with the aEC-negative group [5(33%) patients] (p < 0.05). CONCLUSIONS--Patients with BD have a high prevalence of aEC when microvascular endothelial cells are used in the assay. These antibodies seem to be a marker of disease activity in this condition, previously considered as negative for autoantibodies.